Pengaruh Pembangunan Desa terhadap Penanggulangan Kemiskinan di Indonesia - Farida, Alfiani; Arifuddin, Muhammad Hasbi; Rahimi, Nina; Kamarni, Neng (Fakultas Ekonomi Universitas Samudra, 2022)
Poverty harms development, so we must address it immediately. The poor in Indonesia are more distributed in rural areas than urban areas, so they must pursue rural development to alleviate poverty. This study aims to analyze the impact of rural development on poverty alleviation in Indonesia. In this study, the Village Development Index (IPD) consists of five dimensions, namely essential services, infrastructure conditions, accessibility, publik services, and governance. The research method uses regression analysis with unit analysis for 434 provinces/cities in Indonesia. The results show that two dimensions, i.e. essential services and publik services have a negatif and significant impact on poverty in Indonesia. Other variables that have a significant impact on poverty reduction in Indonesia are economic growth and the Human Development Index.